Integrasi Penggunaan Teknologi dalam Strategi Pembelajaran PAI untuk Membentuk Kompetensi 4C Peserta Didik Era Digital - Sakdiyah Sakdiyah; Widna Widna; Gusmaneli Gusmaneli (Lembaga Pengembangan Kinerja Dosen, 2025)
This study aims to analyze the integration of technology in Islamic Religious Education (IRE) as a strategic effort to develop students’ 21st-century skills, particularly the 4Cs: Critical Thinking, Creativity, Communication, and Collaboration. In the digital era, educators are required to adapt learning approaches that not only convey religious knowledge but also empower students with relevant skills for navigating modern challenges. Employing a qualitative research method through a comprehensive literature review, this study explores various scholarly works that discuss the role of digital technology in supporting the development of 21st-century competencies within the IRE framework. The analysis reveals that technology-enhanced IRE learning fosters student engagement, strengthens critical and creative thinking processes, facilitates interactive communication, and encourages collaborative learning environments. Furthermore, the integration of technology allows for the contextualization of Islamic values in formats that resonate with the current digital-native generation. This synergy between religious instruction and digital innovation supports the holistic development of learners, ensuring they are intellectually equipped and spiritually grounded. The findings highlight the necessity for educators to design innovative, flexible, and value-based learning strategies that align with technological advancements while preserving the core principles of Islamic education. Ultimately, this research offers valuable insights for practitioners, policymakers, and curriculum developers in enhancing the relevance and effectiveness of Islamic Religious Education in the 21st century.